Femininity and accompaniment in suffering - Flores Jiménez, Beatriz (2020)
One of the manifestations of evil in man is undoubtedly the experience of suffering and pain, which inevitably occurs in one way or another throughout life, showing man his creative reality. In these moments, the presence of a company is necessary, not only external or superficial, but one that can penetrate in a way inside and from there "be" with the person who suffers. The feminine being then appears as available to meet, welcome and donate herself to the sufferer. It is that women as a person have their own peculiarities from their own corporality, through their motherhood, to their most transcendental consideration that contribute to the process of appreciation and sense of human suffering.